CORRELATION OF MORPHOANATOMICAL TRAITS WITH LODGING RESISTANCE IN SPRING WHEAT IN THE MIDDLE VOLGA REGION - V. G. Zakharov; V. V. Syukov; O. D. Yakovleva (Вавиловский журнал генетики и селекции)
The study concerns the variability of dual lodging resistance and morphoanatomical indices of the culm in 17 spring wheat varieties. Factor, path, and multivariate regression analyses indicate that reliable direct and indirect contributions to plant resistance to lodging are made by the lengths of the second and third lower internodes, the sum of their lengths, and the fractural strength of the culm at lower internodes. It is shown that the selection for lodging resistance in spring wheat can be done in early generations on the base of the lengths of lower internodes.